2022
DOI: 10.1111/padr.12474
|View full text |Cite
|
Sign up to set email alerts
|

Women's Low Employment Rates in India: Cultural and Structural Explanations

Abstract: Indian women's labor force participation rates have long demonstrated a U‐shaped relationship with their education, rather than a more conventional positive linear relationship. The low rates of employment for moderately educated women are usually explained either as a result of the cultural stigma of women's employment in a patriarchal society or because of the lack of demand from white‐collar and light manufacturing jobs for women with middle levels of education. Using especially well‐suited data from two wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Conversely, various empirical studies on employment trends documented that the rate of women’s labor force participation (LFP) in India has been declining continuously because of low literacy rate, sociocultural stigma and skill mismatch, especially in manufacturing and agriculture sectors due to high mechanization in these sectors. Moreover, low local market jobs and security are also major issues for declining rate of women LFP (Chatterjee and Vanneman, 2022; Mehrotra and Parida, 2017; Sarkar and Dutta, 2022). A similar trend has been observed in the Female Entrepreneurship Index (FEI) of Global Entrepreneurship and Development Institute (GEDA), wherein India stood at 70th position out of 77 countries covered in the study to measure the growth of potential female entrepreneurs across the world (Terjesen and Lloyd, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, various empirical studies on employment trends documented that the rate of women’s labor force participation (LFP) in India has been declining continuously because of low literacy rate, sociocultural stigma and skill mismatch, especially in manufacturing and agriculture sectors due to high mechanization in these sectors. Moreover, low local market jobs and security are also major issues for declining rate of women LFP (Chatterjee and Vanneman, 2022; Mehrotra and Parida, 2017; Sarkar and Dutta, 2022). A similar trend has been observed in the Female Entrepreneurship Index (FEI) of Global Entrepreneurship and Development Institute (GEDA), wherein India stood at 70th position out of 77 countries covered in the study to measure the growth of potential female entrepreneurs across the world (Terjesen and Lloyd, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Goldin (1994) discusses how social and cultural contexts determine a married woman's labour supply decisions. Chatterjee and Vanneman (2022) find only modest support for stigma, measured by the observance of purdah system in India, on women's employment. Afridi et al (2018) found that education played a substantial role but did not find strong evidence that observable factors like socio-religious identities that are linked with the social stigma of women working outside the house play a substantial role in women's labour force participation.…”
Section: India Patriarchy Indexmentioning
confidence: 80%
“…Researchers have examined the extent to which cultural contexts and norms can explain women's labour force participation (Afridi et al, 2024;Chatterjee & Vanneman, 2022;Goldin, 1994;Jayachandran, 2021). Goldin (1994) discusses how social and cultural contexts determine a married woman's labour supply decisions.…”
Section: India Patriarchy Indexmentioning
confidence: 99%